2020
DOI: 10.1039/d0gc03240a
|View full text |Cite
|
Sign up to set email alerts
|

New ternary deep eutectic solvents for effective wheat straw deconstruction into its high-value utilization under near-neutral conditions

Abstract: The new synthesized DES is used to reduce, which significantly reduces the maintenance cost of biomass refining equipment and provides a feasible way for biomass resource utilization under near-neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…To this aim, harsher experimental conditions, involving higher operating temperatures and longer extraction times, were adopted, following literature reported procedures [43,44]. For comparison, the efficacy of ChCl:LA2 was also tested, having this latter being reported to exhibit a strong selective dissolving ability toward lignin from different biomasses [61,62]. Treatment of CWF with the two DESs was performed at 120 • C for 8 h. The dark brown liquid obtained was then subjected to two different precipitation protocols, involving addition of 0.01 M HCl or of an acetone/water mixture [44], both leading to a brown solid in 10% w/w yield (although 43-48% w/w of the starting CWF was dissolved).…”
Section: Cwf Lignin Extraction By Treatment With Dess Under Harsh Con...mentioning
confidence: 99%
“…To this aim, harsher experimental conditions, involving higher operating temperatures and longer extraction times, were adopted, following literature reported procedures [43,44]. For comparison, the efficacy of ChCl:LA2 was also tested, having this latter being reported to exhibit a strong selective dissolving ability toward lignin from different biomasses [61,62]. Treatment of CWF with the two DESs was performed at 120 • C for 8 h. The dark brown liquid obtained was then subjected to two different precipitation protocols, involving addition of 0.01 M HCl or of an acetone/water mixture [44], both leading to a brown solid in 10% w/w yield (although 43-48% w/w of the starting CWF was dissolved).…”
Section: Cwf Lignin Extraction By Treatment With Dess Under Harsh Con...mentioning
confidence: 99%
“…More recently, another kind of DES has also been introduced, Type V, which is composed only by nonionic molecular HBAs and HBDs [37]. Over the last years, ternary DES, prepared by the mixture of one type of HBA and two types of HBD, have also been an important research topic that have already been applied in different areas such as carbon dioxide absorption [38], extraction of lignin [39], and reversible absorption of NH 3 [40].…”
Section: Deep Eutectic Solventsmentioning
confidence: 99%
“…Density functional theory showed that BA could bond with -OH similar to Cl − , and it occupied more effective sites than Cl − , breaking the hydrogen-bonding network between lignin and cellulose. Importantly, the DES can be used multiple times without significantly reducing its efficiency, and its structure and properties remain virtually unchanged throughout [89].…”
Section: Ternary Desmentioning
confidence: 99%